The Admissibility of Scientific Expert Evidence Under Indonesian Criminal Justice System - Wanodyo Sulistyani (Sriwijaya Law Review, 2019)
In many cases, such as corruption and forestry-related crimes, an expert has a significant role in explaining the impact of the crime. For instance, scientific expert evidence is required to disclose about the ecological destruction that occurred due to the defendant's criminal activities. In practices, the issue with scientific expert evidence is supposed to be about its admissibility in court. For this issue, the U.S. Court applies Rules of Evidence in considering the admissibility of scientific expert evidence at trial. Those are some requirements (prong test) to be met before expert testimony is admissible. In contrast, the Indonesian Criminal Procedural Law (KUHAP) or other laws do not set any prong test for presenting specialist scientific evidence to be acceptable. Lack of such proof may impact criminal justice process reliability and place expert under vulnerable position. Therefore, this paper will explore the issue on scientific expert evidence under Indonesian criminal law as well as its consequences and impacts for the Indonesian criminal justice process.